High Telomerase Activity Correlates with the Stabilities of Genome and DNA Ploidy in Renal Cell Carcinoma - Izumi, Hideki (Nature Publishing Group, 2002)
Malignant tumors have telomerase activity, which is thought to play a critical role in tumor growth. However, the relation between telomerase activity and genomic DNA status in tumor cells is poorly understood. In the present study, we examined telomerase activity in 13 clear cell type renal cell carcinomas (CRCCs) with similar clinicopathologic features by telomeric repeat amplification protocol assay (TRAP). Based on TRAP assay results, we divided the CRCCs into two groups: a high telomerase activity group and a low/no telomerase activity group. We then analyzed genomic aberration, DNA ploidy, and telomere status in these two groups by comparative genomic hybridization (CGH), laser scanning cytometry (LSC), and telomere-specific fluorescence in situ hybridization (T-FISH), respectively. CGH showed the high telomerase activity group to have fewer genomic changes than the low/no telomerase activity group, which had many genomic aberrations. Moreover, with LSC, DNA diploid cells were found more frequently in the high telomerase activity group than in the low/no telomerase activity group. In addition, T-FISH revealed strong telomere signal intensity in the high telomerase activity group compared with that of the low/no telomerase activity group. These results suggest that telomerase activity is linked to genomic DNA status and that high telomerase activity is associated with genomic stability, DNA ploidy, and telomere length in CRCC.